PERLINDUNGAN HUKUM BAGI NOTARIS UNTUK MENJAGA KERAHASIAAN ISI AKTA YANG DIPERBUATNYA DALAM PERKARA PIDANA (STUDI DI PEMATANGSIANTAR) - GRACE NOVIKA RASTA (PREMISE LAW JURNAL, 2015)
Notary is obliged to keep secret the contents of the deed he/she made or made before him/her that is bound to the oath / occupational confidentiality and the dutyof a Notary, but if the deed he made has indications of a criminal act, then the notary must remove or ignore his/her obligation to keep secret the contents of the deed due to meeting the public interest to help smooth the legal process to achieve legal certainty. Notary has the right of refusal as a form of legal protection for his/heroffce/position and in the case of examination in relation to the deed he/she made, the notary can plead for the Derivatives of the Minutes of Interrogation at Court related to the information he/she gave in the court trial. Lack of understanding on the side of Notary and law enforcement officers often leads to misunderstandings during the examination of a Notary related to the deed made before him/her that have indications of criminal matters. So it is necessary to have the same knowledge and understanding in order to avoid misunderstandings when examininga Notary related to the criminal case concerning the deed he/she made. Keywords: Notary, Occupational Confidentiality, Criminal Case